2017
DOI: 10.4038/sljch.v46i1.8237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breast feeding techniques among postnatal mothers and effectiveness of intervention: Experience in a tertiary care centre

Abstract: Background: Effective breastfeeding (BF) is a function of proper positioning and attachment of a child to mother's breast. However, there is paucity of data on mothers' skills of positioning and attachment of baby and effectiveness of educating the same in the initial days of hospital stay. Objectives:To assess the effectiveness of educating the postnatal mothers who were feeding with incorrect positioning and attachment on the correct BF technique and to identify the mothers needing support and the factors af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 3 publications
4
14
2
1
Order By: Relevance
“…Mothers who had secondary school education and above were 2.3 times more likely to practice effective BFT compared to their counterparts. This was in accordance with a study done in Indian East Delhi, west Bengal Kolkata hospital, Saudi Heraa general hospital and Sri Lanka [ 11 , 23 , 32 , 33 ]. This is due to the fact that more educated mothers had strong intention and willingness to breastfeed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mothers who had secondary school education and above were 2.3 times more likely to practice effective BFT compared to their counterparts. This was in accordance with a study done in Indian East Delhi, west Bengal Kolkata hospital, Saudi Heraa general hospital and Sri Lanka [ 11 , 23 , 32 , 33 ]. This is due to the fact that more educated mothers had strong intention and willingness to breastfeed.…”
Section: Discussionsupporting
confidence: 92%
“…This was true in Bangladesh among two groups of postpartum mothers, there were a significant positive association with practice of effective BFT among mothers who received both early and late postnatal care visit compared to only one visit by Community health worker [ 24 ]. This is likely to be due to the fact that psychological support for breastfeeding mothers through early counselling and hands-on support for achieving proper techniques, particularly position and attachment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that young mothers are offering breastfeeding to their infants' inappropriately, which could ultimately adversely affects their health. Similar ndings were reported from studies done in a teaching hospital in coastal Karnataka, India, Indonesia, and Libya (11,13,31,36). This shows an increase in mothers' age rises the experience of BFT and their con dence in child handling.…”
Section: Discussionsupporting
confidence: 86%
“…It may probably be due to educating mothers before the initiation of breastfeeding, which was done in the present and supporting study. As Nagendra et al, 21 and Tella et al, 22 also concluded that educating the postnatal mothers improves the position and the attachment of the baby to the breast.…”
Section: Discussionmentioning
confidence: 94%